(untitled) (Journal of Human Sciences, 2026)
This study aims to clarify the role of the Jaghbub Oasis in the resistance movement against the Italian occupation during the period 1911–1931 CE, by analyzing its strategic, military, and religious importance in the course of the Libyan national resistance. The study reached several key conclusions, most notably that the Jaghbub Oasis constituted a pivotal center for leading and organizing the resistance, and its geographical location contributed to securing communication and supplies between the resistance fighters and the various areas of jihad. Its religious institutions also played an active role in mobilizing the resistance and preparing its leaders. The results also showed that the Italian occupation’s targeting and occupation of the oasis was part of a colonial strategy aimed at breaking the organizational structure of the resistance and isolating its leadership. The fall of Jaghbub represented a significant turning point in the course of the resistance, without ending it, but rather contributing to a redistribution of military power centers, particularly in the Green Mountain region. The study’s originality lies in its treatment of the Jaghbub Oasis as a significant historical actor in the jihad movement, rather than merely a geographical setting for events. This is achieved through an analytical connection between geography, jihadist organization, and Italian colonial policy, thus offering a valuable scholarly contribution that fills a gap in historical studies on the Libyan jihad. The study employs a descriptive and analytical historical methodology in presenting and analyzing historical facts.